REVITALISASI KARANG TARUNA MELALUI MEDIA DIGITAL GUNA MENGOPTIMALKAN KINERJA - Sihotang, Yosi Fransiska; Syifa, Lisa Nurul; Luthfie, Elfrida Fahrizky; Shafira, Shafa; Yamrohimi, Rizki Ananda; Aksal, Muhammad; Aji, Iqbal Permana; Nurdiarti, Rosalia Prismarini (Universitas Mataram, 2024)
The revitalization of the Youth Organization is an important key to restoring the passion and activeness of youth organizations in Tambalan Village, Pleret, Bantul after a period of vacuum due to the COVID-19 pandemic. Through a digital approach, especially the use of social media and websites, this activity aims to strengthen communication, collaboration, and youth participation. This study shows that the main challenge faced is the lack of information management and documentation of activities that can affect the effectiveness of the organization. Therefore, it is also necessary to play an active role in youth members in using and utilizing the existence of social media. The implementation of the activity proves that through socialization, training, and development of digital platforms, Karang Taruna Surya Ndadari has succeeded in increasing interaction and information coverage. Thus, revitalization through digital media is expected not only to improve organizational performance, but also to encourage active community participation in various social activities. This is expected to be able to restore the strategic role of youth organizations in community development.